The Effect of the Birthing Ball on Duration of the First Stage of Labour in Primigravida at Utama Barokah Clinic, Bandung City in 2021 - Oktafiani, Feni; Suciawati, Anni; Rukmaini, Rukmaini (Muhammadiyah Medical Journal, 2021)
Background: Labour and birth are physiological and normal events. The process is considered to be normal if it takes 37-42 weeks without any complications. Non-pharmacological methods to speed up the progress of labour include birthing ball exercises. The Birthing ball exercise is a technique to help the progress of labour that can be used during the first stage of labour. Until now, birthing balls are not widely known and not common, even though birthing balls are very effective in accelerating the birth process. The advantage of using the birthing ball is that it increases blood flow to the uterus, placenta and baby, and provides comfort for the knees and ankles. Purposes: The purpose of this study was to determine the average length of the first stage of labour in primigravida using a birthing ball and those not using a birthing ball and the effect of the birthing ball on the duration of the first stage of labour in primigravida. Method: This study uses a quasi-experimental method with a Randomized Two-Group design, Post-test only. This study was held at Utama Barokah Clinic, Bandung from June to July 2021. Result: The research sample was 30 respondents, primigravida during the first stage of labour with data analysis using the Mann Whitney test, and the p value 0.05 was obtained. Conclusion: There was a difference in the average length of the first stage of labour in primigravida using a birthing ball and those not using a birthing ball.